Comparison of Sepsis in Covid 19 Infected Patients on Therapeutic Plasma Exchange Vs Tocilizumab - Hussain, Amina; Fazal, Imran; Uruj, Sana; Saleem, Asim; Sarwar, Natasha (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the presence of sepsis in COVID 19 infected patients on therapeutic plasma exchange vs Tocilizumab managed at Pak Emirates Military Hospital Rawalpindi Study Design: Comparative Prospective study Place and Duration of Study: Pak Emirates Military hospital Rawalpindi, from Feb 2021 to May 2021 Methodology: Patients who were diagnosed with COVID-19 on polymerase chain reaction and were oxygen dependent but not mechanical ventilation dependent were included in the study. They were randomly divided into two groups. Group I received 3-5 sessions of plasma exchange while group II received 1-2 doses of Tocilizumab. They were followed up for 10 days to look for presence of sepsis on basis of pro-calcitonin. Type of treatment used and other factors were correlated with presence of sepsis among the target population. Results: Out of 350 patients included in the study 201 (57.4%) were male while 149 (42.6%) were female. Mean age of the study participants was 49.69 ±9.456 years. 287 (82%) had procalcitonin within range and no evidence of bacterial sepsis while 63 (18%) were diagnosed as having sepsis on the basis of raised pro-calcitonin levels. Advanced age, presence of comorbidities and use of Tocilizumab had statistically significant relationship (p-value<0.05) with presence of sepsis among the patients managed for severe COVID 19. Conclusion: Bacterial sepsis was found in significant number of patients with severe COVID 19 illness undergoing therapeutic plasma exchange or receiving Tocilizumab. Patients more than 40 years of age or having comorbid medical illnesses or receiving Tocilizumab instead of plasma...